The Relationship Between Corporate Social Responsibility, Capital Structure, And Profitability On Firm Value - Nurfani Amelia Putri; Mukhzarudfa Mukhzarudfa; Aulia Beatrice Brilliant (Journal of Innovative and Creativity, 2025)
This study endeavours to investigate the nexus among Corporate Social Responsibility, Capital Structure, and Profitability in relation to Firm Value. Employing a purposive sampling approach, the research focuses on energy-sector entities listed on the Indonesia Stock Exchange (IDX) over the 2021–2024 timeframe. The dataset was procured from the official IDX portal (www.idx.co.id) and the respective corporations’ authorised websites. Analytical procedures were conducted through a correlation examination utilising Stata version 17. The empirical outcomes reveal that both Corporate Social Responsibility and Capital Structure exhibit an exceedingly weak and statistically non-significant association with Firm Value, whereas Profitability demonstrates a moderately robust and statistically significant positive correlation with Firm Value.